Synthesis and in-vitro Evaluation of S-allyl Cysteine Ester - Caffeic Acid Amide Hybrids as Potential Anticancer Agents (2019)
ABSTRACT: We have synthesized a series of S-allyl cysteine ester-caffeic acid amide hybrids and evaluated them in order to determine their possible anticancer activity and selectivity in colorectal cancer, which is still one of the leading causes of morbidity and mortality worldwide. All compounds were tested against SW480 human colon adenocarcinoma cells and the non-malignant CHO-K1 cell line. Among the tested compounds, hybrids 6e, 9a, 9b, 9c, and 9e exhibited the highest effect on viability (IC50 SW480-48h= 0.18, 0.12, 0.12, 0.11, and 0.12 mM, respectively) and selectivity (SI = 10.3, 1.5, >83.33, >90.91 and >83.33, respectively) in a time- and concentration-dependent manner. Besides, our results were even better as regards lead compounds (S-allyl cysteine and caffeic acid) and the standard drug (5-FU). Additionally, these five compounds induced mitochondrial depolarization that could be related with anapoptotic process. Moreover, hybrids 6e, 9a, and 9e induced cell cycle arrest in G2/M phase, and compound 9c in S- phase, which suggests that these hybrid compounds could have also a cytostatic effect in SW480 cell line. The SAR analysis showed that hydroxyl groups increased the activity. Besides, there was not a clear relationship between the antitumor properties and the length of the alkyl chain. Since hybrid compounds were much more selective than the conventional drug (5-FU), this makes them promising candidates for further studies against colorectal cancer.